Medical management of vitiligo: a narrative review - Surabhi Sinha; Diksha Agrawal (Pigment International)
Vitiligo is a chronic cutaneous disease presenting with asymptomatic depigmented macular lesions without any signs of inflammation. Since time immemorial, treatment has been sought for this disorder due to the substantial stigma associated with it, more so in patients with skin of color. Vitiligo can be divided into two major clinical types − segmental vitiligo (SV) and non-segmental vitiligo (NSV). The pathophysiological basis for the loss of functional melanocytes resulting in vitiligo includes genetic predisposition, autoimmune mechanisms, and oxidative stress, among others. Thus, combination therapies targeting the autoimmune nature of disease, activation of melanocytes, and reduction of oxidative stress often yield a successful treatment response. There are very few FDA-approved options for vitiligo, and certain recently introduced modalities may modify the way vitiligo is conventionally treated. This review summarizes the conventional as well as the newer medical treatment options for different clinical types of vitiligo.